Application of Internet in Road Traffic Engineering - Dadić, Ivan; Kos, Goran (Promet - Traffic&Transportation, 2012)
The paper deals with the implementation of Internet in trafficengineering with the purpose of improving the professionaland scientific research development of the traffic system in theRepublic of Croatia.Fast growth of the world computer network, Internet, andits applications in almost all the fields of human activities,change the picture of the modern world. The current exchangeof data in all their forms and the daily growth of the network,supplemented by almost incredible amounts of data that can bealmost instantly accessible, indicates that Internet is not just theinfomwtion technology revolution, but that it is a revolutionper se. More than 100 million computers are estimated to benetworked beginning of the 21’ century.Internet seems almost as if it were created for the purposesof knowledge and expe1ience exchange in traffic, a relativelyyoung scientific branch. 11 can be concluded that the presenceof traffic engineers in Internet is today’s reality and tomon·ow’snecessity.